ANALISIS STRATEGI PRODUKSI TEMPE TERHADAP PENYESUAIAN HARGA BAHAN BAKU - Maghfiroh, Anggun Wasiatul (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the strategy for adjusting the price of raw materials on tempe producers. The technique used in this research is descriptive qualitative. The object of this research is the owner of tempe producers in Jantok Village, Purwoasri District, Kediri Regency. The research variable is the impact of the increase in the price of raw materials and the strategy of tempe products. This study used interviews with the owners of tempe producers in Jantok Village, Purwoasri District, Kediri Regency. The results of this study indicate that the raw material for making tempeh using soybeans is very influential on the costs that must be incurred by tempe producers, additional capital by tempe producers took the initiative to reduce the size of tempe from tempe size of 4.3 cm into tempeh size to 3.5 cm. The strategy adopted by tempe producers is to travel between villages and deposit them to restaurants.